2021
DOI: 10.4209/aaqr.2020.03.0101
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Activity in PM2.5 in Indoor Air: As an Index of Air Quality Level

Abstract: Bioaerosols are a major source of pollution in indoor environments, where people spend approximately 90% of their time, and the microorganisms adhered to PM2.5 adversely affect human health. However, most research has focused on the concentration of these aerosols and the factors that influence it rather than the correlation between microbial activity and air quality. Thus, this study used a modified technique of fluorescein diacetate (FDA) hydrolysis to evaluate the activity of microorganisms in the PM2.5 dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…PM2.5 is ubiquitously existed in the indoor and outdoor environment (Bai et al, 2021;Navinya et al, 2020;Yu et al, 2021). Several types of environmental pollutants, including metals, organic compounds, and microbes, are contaminated on PM2.5 (Chen et al, 2021;Shen et al, 2020;Siudek and Ruczyńska, 2021;Vega et al, 2021). To raise the public concerns, PM2.5 has been demonstrated to cause the adverse effects on animal models and human bodies (Chao et al, 2018;Chung et al, 2020;Zhang et al, 2020).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…PM2.5 is ubiquitously existed in the indoor and outdoor environment (Bai et al, 2021;Navinya et al, 2020;Yu et al, 2021). Several types of environmental pollutants, including metals, organic compounds, and microbes, are contaminated on PM2.5 (Chen et al, 2021;Shen et al, 2020;Siudek and Ruczyńska, 2021;Vega et al, 2021). To raise the public concerns, PM2.5 has been demonstrated to cause the adverse effects on animal models and human bodies (Chao et al, 2018;Chung et al, 2020;Zhang et al, 2020).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…6,7 There are a number of existing studies that assess indoor particulate matter (PM) pollution, however a frequent limitation of these studies is monitoring is limited to only 1 or 2 locations within a property (oen a kitchen or main living area). 4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] 35 reported a comprehensive multi-room study with multiple sensors, yet this was limited to PM 2.5 (particles with aerodynamic diameters <2.5 mm) as the sensors were not calibrated for the PM 1 & PM 10 (particles with diameters <1 mm and <10 mm respectively) fractions that they also monitored. Few previous studies have used IoT networks for monitoring, and those that did, tended to use IoT networks that are reliant on gateway or WiFi technology thus limiting deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Chen et al . (2021b) have shown that the indoor microbial activity in winter is closely related to the window ventilation state and indoor environment. Meng et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, microbial activity increased in heavy and severe pollution (>200). Studies of Chen et al (2021b) have shown that the indoor microbial activity in winter is closely related to the window ventilation state and indoor environment. Meng et al (2016) found that microbial activity increases with an increase in particle size, but there are also studies (Chen et al, 2021a) that have found no significant difference in microbial activity between PM 2.5 and PM 10 .…”
Section: Introductionmentioning
confidence: 99%